From Corn to Cassava: Unveiling PLA Origins for Sustainable 3D Printing - Fatchurrohman, Nanang; Muhida, Rifki; Maidawati (Jurnal Teknologi, 2023)
The focus of this paper is to review the polylactic acid (PLA) sourcing for 3D printing and investigating with a specific emphasis on corn starch, sugarcane, and cassava starch. PLA is recognized for its biodegradable nature and versatility as a thermoplastic, has witnessed a notable evolution in the global context of material selection for 3D printing. While regions such as the United States and Canada have traditionally derived PLA from corn starch, there is a growing trend in Asia where cassava starch have emerged as prominent alternatives. This study seeks to discover the complexities of the of PLA origins, looking into the sustainability considerations that contribute to the selection of source materials. By shedding light on the diverse trajectories of PLA sourcing, this study provides valuable insights into the ever-changing dynamics of material preferences for 3D printing on a worldwide scale. Moreover, the understandings generated through this study are composed to play a pivotal role in shaping the trajectory of future practices in additive manufacturing. As the industry continues to evolve and grapple with the imperative of environmental responsibility, a nuanced understanding of the sustainability dimensions of PLA sourcing becomes a compass guiding researchers, practitioners, and manufacturers toward ecologically sound choices. Ultimately, the study serves as a valuable resource, empowering participants to navigate the complex landscape of PLA-based 3D printing with a thorough judgement on sustainability, thereby fostering a more environmentally responsible future for additive manufacturing.